2022
DOI: 10.1155/2022/9902905
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Activity of trans-Anethole in Mice

Abstract: Epilepsy is a chronic neurological disorder affecting 1-2% of world population, and one-third of patients are refractory to pharmacological treatment. This fact has stimulated research for new antiepileptic drugs and natural products have been an important source. trans-Anethole (TAN) is a phenylpropanoid, component of some essential oils, extracted from plants, and its effects have been little studied. Therefore, this study is aimed at investigating the TAN effect in classic seizure models and evaluate the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Anethole (1-methoxy-4-propenylbenzen) is a natural component found in plants like anise, fennel, and dill ( Yu et al, 2022 ). Previous studies have been reported various pharmacological effects for anethole including antioxidant, anti-inflammatory, anti-nociceptive and antiepileptic properties ( da Guedes et al, 2022 , Kang et al, 2013 , Ritter et al, 2013 , Ghasemi-Dehnoo et al, 2022 , Pandit et al, 2022 ). Previous studies have been demonstrated that anethole possessed neuroprotective effects in various neurological disorders ( Vastegani et al, 2023 , Chang et al, 2022 , Salimian et al, 2022 , Raman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anethole (1-methoxy-4-propenylbenzen) is a natural component found in plants like anise, fennel, and dill ( Yu et al, 2022 ). Previous studies have been reported various pharmacological effects for anethole including antioxidant, anti-inflammatory, anti-nociceptive and antiepileptic properties ( da Guedes et al, 2022 , Kang et al, 2013 , Ritter et al, 2013 , Ghasemi-Dehnoo et al, 2022 , Pandit et al, 2022 ). Previous studies have been demonstrated that anethole possessed neuroprotective effects in various neurological disorders ( Vastegani et al, 2023 , Chang et al, 2022 , Salimian et al, 2022 , Raman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have postulated that several etiologies are involved in the pathophysiology of seizures. A disturbed balance between neuronal excitation and inhibition (glutamate/γ-aminobutyric acid (GABA) equilibrium) plays a major role in seizure development [5][6][7]. Glutamate and GABA transmission can curb the release and/or uptake of other neurotransmitters, affecting neuronal network activity and maintaining normal balance at the cellular level [8].…”
Section: Introductionmentioning
confidence: 99%